Internal hernia beneath the left external iliac artery after robotic-assisted laparoscopic prostatectomy with extended pelvic lymph node dissection: a case report - Shigeo Ninomiya; Shota Amano; Tadashi Ogawa; Yoshitake Ueda; Norio Shiraishi; Masafumi Inomata; Katsuhiro Shimoda (Surgical Case Reports, 2019)
Abstract Background Formation of an internal hernia beneath a skeletonized pelvic vessel after pelvic lymph node dissection is extremely rare. We report a case of an internal hernia formation beneath the left external iliac artery after a robotic-assisted laparoscopic prostatectomy with extended pelvic lymph node dissection. Case presentation A 72-year-old man visited our hospital complaining of severe lower abdominal pain. On physical examinations, his abdomen was distended and tympanitic with rebound tenderness and muscular defense. Abdominal non-enhanced computed tomography showed a small bowel obstruction with marked ascites. A coronal non-enhanced computed tomography image revealed thickened loops of small bowel with surrounding mesenteric edema in the left lower quadrant. Enhanced computed tomography was not performed because we decided to perform urgent surgery with a diagnosis of strangulated small bowel obstruction based on physical examination and the computed tomography findings. The patient underwent urgent laparotomy at which time bloody ascites was seen in the peritoneal cavity. The ileum, which was approximately 60 cm proximal to the ileocecal junction, formed a closed loop beneath the left external iliac artery. The incarcerated ileum, 120 cm in length, appeared non-viable with a color change of the ileum to black. We therefore resected the strangulated ileum for a length of 120 cm and performed a functional end-to-end anastomosis. The orifice beneath the left external iliac artery was about 4 cm in diameter. We did not close the orifice because of the risk of injuring the left iliac artery. The postoperative course was uneventful, and the patient was discharged from our hospital 10 days after surgery. Presently, the patient is doing well 5 months after surgery without recurrent disease. Conclusion We report an extremely rare case of internal hernia formation beneath the left external iliac artery after a robotic-assisted laparoscopic prostatectomy with extended pelvic lymphadenectomy. Awareness of such complication and early surgical treatment are important when treating patients with this rare occurrence.